Distributions of phenolic acid antioxidants between the interfacial and aqueous regions of corn oil emulsions—a commentary. Issue 11 (16th July 2015) - Genot, Claude
Abstract : Being capable of optimizing the usage of antioxidants is a challenge for any industry concerned with formulating food and non‐food products because it will affect its competitiveness and the product's attractiveness in response to consumer demand. This is also a challenge for scientists who remain puzzled by the unpredictable oxidative behavior of real, complex food, and non‐food matrices. Laurence Romsted and Carlos Bravo‐Diaz have developed some years ago a pseudophase kinetic model to determine the partitioning of chain‐breaking antioxidants in micellar systems and emulsions stabilized by surfactants. In this article, with Sonia Lasada‐Barreiro they used the pseudophase model to determine the partitioning of two phenolic antioxidants (gallic acid and caffeic acid) in a model oil‐in‐water emulsion with increasing surfactant concentrations and at different pH values. This commentary underlines the importance of the pseudo‐phase model and the present work to achieve a better use of antioxidants. It is also suggested that the enigma of antioxidant efficiency in complex systems is far from completely solved.